Analisis semantik puisi Gerimis Jatuh karya Sapardi Djoko Damono - Fithonah, Mahrotul (Maliki Interdisciplinary Journal, 2024)
Poetry is one of the literary works that is commonly used. There are many aesthetic elements and meanings contained in poetry, so sometimes some people have difficulty understanding the implied meaning of a poem. Even many people misunderstand the meaning in poetry. Therefore, this study aims to determine the semantics (meaning of language) contained in the poem Gerimis Jatuh by Sapardi Djoko Damono. This study used qualitative descriptive method. The techniques used to collect data are library and observation techniques, based on the results of the analysis, the poetry Drizzle Falls has 5 semantic meanings including: 6 words have lexical meanings, 3 words have grammatical meanings, 9 words mean figuratively, 5 words have referential meanings and 2 have non-referential meanings. The end of this analysis can be concluded that the poem Drizzle Falls describes a calm and contemplative atmosphere of nature. Through drizzling rain, Sapardi expresses deep feelings about life, time, and memories. This research found that the poem "Drizzle Falling" by Sapardi Djoko Damono has diverse and profound meanings. But it should be underlined that in 1 poem can have different interpretations of meaning or substance, depending on the background and degree of understanding of a reader.